Effects of AMF on plant nutrition and growth depend on substrate gravel content and patchiness in the karst species Bidens pilosa L - Shen, Kaiping; He, Yuejun; Xu, Xinyang; Umer, Muhammad; Liu, Xiao; Xia, Tingting; Guo, Yun; Wu, Bangli; Xu, Han; Zang, Lipeng; Gao, Lu; Jiao, Min; et al. (Frontiers in Plant Science, 2022)
Karst ecosystems represent a typical heterogeneous habitat, and it is ubiquitous with varying interactive patches of rock and soil associated with differential weathering patterns of carbonate rocks. Arbuscular mycorrhizae fungi (AMF) play an important role in regulating plant growth and nutrition in heterogeneous karst habitats. However, it remains unclear how AMF affects the growth and nutrition of plants in heterogeneous karst soil with varying patches and weathering gravel. A heterogeneous experiment with Bidens pilosa L. was conducted in a grid microcosm through patching karst soil with different gravel contents. The experimental treatments included the AMF treatments inoculated with (M+) or without (M-) fungus Glomus etunicatum; the substrate patchiness treatments involved different sizes of the homogeneous patch (Homo), the heterogeneous large patch (Hetl), and the heterogeneous small patch (Hets); the substrate gravel treatments in the inner patch involved the free gravel (FG), the low gravel (LG) 20% in 80% soil, and the high gravel (HG) 40% in 60% soil. Plant traits related to growth and nutrients were analyzed by comparing substrate gravel content and patch size. The results showed that AMF was more beneficial in increasing the aboveground biomass of B. pilosa under the LG and HG substrates with a higher root mycorrhizal colonization rate than under the FG substrate with a lower root mycorrhizal colonization rate. AMF enhanced higher growth and nutrients for B. pilosa under the LG and HG substrates than under the FG substrate and under the Hets than under the Hetl. Moreover, AMF alleviated the limited supply of N for B. pilosa under all heterogeneous treatments. Furthermore, the response ratio LnRR of B. pilosa presented that the substrate gravel promoted the highest growth, N and P absorption than the substrate patchiness with M+ treatment, and the gravel content had a more effect on plant growth and nutrition as compared to the patch size. Overall, this study suggests that plant growth and nutrition regulated by AMF mainly depend on the substrate gravel content rather than the spatial patchiness in the heterogeneous karst habitat.